Optimal Control of the Cascaded Kainji-Jebba Hydroelectric Power Station Based on Conjugate Gradient - Ogunbiyi, Olalekan; Thomas, Cornelius T.; Omeiza, Isaac O. A.; Akanni, Jimoh; Olufeagba, Benjamin J. (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Electricity supply in Nigeria has been far below the estimated demand and the installed capacity of the plants. Hence, there has been continuous research on improving the performance of the existing plants, but the government mainly focuses on increasing the installed capacity. This paper presents the determination of the optimal release of water to maximize the energy generation potential of the cascaded Kainji-Jebba hydroelectric power station in Nigeria. The problem was formulated as an optimal control problem with an objective of minimizing the deviation of the head of the Jebba reservoir within a set limit. A conjugate gradient algorithm was then used as a direct solution to the optimal control problem. The computed control law and the resulting state trajectories of 2% error affirm the solution to be genuine and reliable. The algorithm is recommended for use in the design of a real-time optimal controller for the system and a decision guide for the operators.